The Influence of Facilities and Service Quality on Public Satisfaction at the East Binjai District Office - Siti Aisyah Nasution; Elida Elfi Barus (SEAN Institute, 2026)
Excellent public service is a key indicator of regional government performance in supporting community welfare and facilitating public needs. The East Binjai Sub-district Office, as the frontline of administrative services at the sub-district level, often faces complaints related to inadequate facilities and suboptimal service quality, which affects the level of community satisfaction. This study aims to analyze the influence of facilities and service quality on community satisfaction at the East Binjai Sub-district Office using a quantitative method with an explanatory survey approach. Data were collected through questionnaires distributed to 30 respondents selected using simple random sampling from the community receiving services. The independent variables in this study are service facilities (X1), including waiting rooms, parking areas, air conditioning, toilets, and queuing systems, and service quality (X2), including responsibility, assurance, empathy, and responsiveness, while the dependent variable is community satisfaction (Y), measured through overall satisfaction, loyalty, and willingness to recommend. Data analysis was conducted using multiple linear regression, t-tests, F-tests, coefficient of determination (R²), and Pearson correlation with SPSS version 26. The results indicated that 72% of respondents expressed satisfaction with the services provided. Facilities (r = 0.645; t = 6.23; p = 0.000) have a significant effect on community satisfaction, contributing 41.6%, while service quality (r = 0.782; t = 9.45; p = 0.000) has a more dominant influence, contributing 61.2%. Simultaneously, both variables (X1 and However, several facility-related aspects were identified as weak, including limited parking space (65%), unclean toilets (58%), and long queues (52%). In conclusion, service quality has a more dominant influence on community satisfaction compared to physical facilities, with the regression model formulated as Ŷ = 12.45 + 0.32X1 + 0.51X2. Based on these findings, it is recommended to optimize the Online Single Submission (OSS) system, enhance civil servant soft skills through training, improve parking and sanitation facilities, and implement QR code-based digital queue systems to increase service efficiency.